Updating Civil Legislation in Accordance with European Quality Standards: The Example of Ukraine - Shyshka, Roman; Shyshka, Oleksandr; Shyshka, Nataliia; Slipchenko, Anatolii; Tkalych, Maxym (DIXI, 2021)
The article is devoted to the study of European quality standards of the law to promote the effectiveness of the work begun in Ukraine on updating the civil legislation. The ability to achieve this goal depends on the quality of the process. Such a process primarily contributes to the assertion of the absolute value of the human person, freedom, democracy, equality, and the priority of man over the state; improving the mechanisms of protection and proper protection of human rights and freedoms, their equality before the law and justice. The latter especially in the context of counteracting the spread of the COVID-19 pandemic, which has led the state of Ukraine (as well as other states) to take steps to limit or reduce human rights and, accordingly, is not always compatible with the rule of law. General and special methods of scientific knowledge were used in this study, namely methods: Analysis and synthesis, systems analysis, formal-logical and structural-functional, along with some empirical methods. The practical significance of the study is that the materials summarized in the research and the conclusions reached by the authors are relevant for foreign legislators, regarding bringing national legislation to global trends in private law and its compliance with the rule of law, including the principle of legal certainty and legitimate expectations. Based on the analysis of the European Court of Human Rights (ECHR) practice and other European Union requirements for the quality of law in Europe, the authors made several conclusions and recommendations on the process of updating the civil legislation of Ukraine. At the same time, the update in its systemic manifestation should concern not only the quality of norms governing certain civil (private) relations, but also the quality of norms regarding acts of the causal interpretation of legal norms, based on the case-law of the echr for national legislation and special requirements.
Keywords: principle of legal certainty; principle of rule of law; quality standards of law; re-codification; p´andemic covid-19